Form, Function and Meaning of “Satua I Siap Selem” (A Cultural Linguistic Review) - Sutarma, I Gusti Putu; Jendra, I Wayan; Adnyana, Ida Bagus Artha; Sukmawati, Ni Made Rai; Suarja, I Ketut (Bali Membangun Bali: Jurnal Bappeda Litbang, 2024)
Purpose: The purpose of this research is to describe the form, function (of language) and meaning of Satua (Folklore) I Siap Selem from a Cultural Linguistic perspective. Research methods: This research is descriptive qualitative in nature using primary data collected using the observation method with the help of note-taking techniques. Data were analyzed using the matching method and the agih method and the results were presented using formal and informal techniques. Results and discussion: The form of Satua I Siap Selem is a discourse in the form of fictional prose. The general function of Satua I Siap Selem is as a means of entertainment, while based on the communicative function of language its functions are informational, expressive, directive, aesthetic and phatic. The implied meaning of Satua I Siap Selem states mutual love and togetherness, mutual respect and mutual help, evil or cunning, ingenuity and responsibility, as well as stupidity. Implications: Satua I Siap Selem contains a good life philosophy and moral messages so it is very good to serve as bedtime entertainment and character education for children.